Foresight for Internationalization of Medical Sciences Universities in Iran in the 2040 horizon - Azadeh Ahmadzadeh Ghasab; Majid Heydari; Mohammad Arab (European Journal of Futures Research)
Abstract The internationalization of medical universities is confronted with various uncertainties due to environmental trends. Therefore, obtaining insight into potential future scenarios is essential for adopting exclusive and effective strategies. Accordingly, this study aims to identify future scenarios for the internationalization of Medical Sciences Universities in Iran (MSUI) in the 2040 horizon. A scenario-based strategic planning approach was employed to create and develop possible scenarios for the internationalization of Iran’s medical universities. This approach followed a four-step framework consisting of scoping, exploring, synthesizing, and scenario building. To develop the scenarios, a combination of futures study methods was employed, including a literature review, expert opinions, cross-impact analysis, morphological analysis, and balance impact analysis. Qualitative data were analyzed using framework analysis and MAXQDA software, while quantitative data were analyzed using EXCEL, MICMAC, and Scenario Wizard software. A total of 61 drivers related to the future of internationalization of medical sciences universities in Iran were identified. Key drivers such as political relations and diplomatic influence, economic sanctions, scientific supremacy, and the knowledge economy were recognized. By configuring the states of these key drivers in the 2040 horizon, a total of 81 possible scenarios were generated. Among these scenarios, 16 were assessed as plausible, with 5 of them being highly probable. These scenarios include evergreen universities, lush universities, blooming season, frost gardens, and dried-up gardens. The analysis of probable future scenarios reveals that the optimistic conditions of the driving forces outweigh those of their pessimistic counterparts, indicating that, at worst, the current situation will persist. Each university could select a probable scenario aligned with its preferred vision to implement within the study timeframe.